214k views
2 votes
Can someone help me i am confused

Can someone help me i am confused-example-1
User Ranch
by
5.7k points

1 Answer

2 votes

Answer:

3. 2

4. f(n) = 3 + 4(n - 1)

Explanation:

3. The general term of the arithmetic sequence is given by:

A(n) = - 14 + (n - 1)(2)

To find the ninth term of this arithmetic sequence, just put
$ n = 9 $ in the general term.

∴ A(9) = - 14 + (9 - 1)(2) = - 14 + 8(2) = -14 + 16 = 2.

Therefore the ninth term in the arithmetic sequence is two.

4. To know which expression represents the given sequence, substitute different values for
$ n $ to conclude.

In Option A, f(n) = 4 + 3(n - 1). Substitute n = 1.

We get f(1) = 4 + 3(0) = 4. This is not the first term in the sequence and can be eliminated.

In Option B, f(n) = 4 + 3n. Substitute n = 1.

We get f(1) = 4 + 3(1) = 7, not 3 so can be eliminated.

Similarly in Option C, we get 7 and could be eliminated.

In Option D, f(n) = 3 + 4(n - 1). Substitute n = 1.

We get f(1) = 3 + 4(1 - 1) = 3, which is the first term in the sequence.

Similarly, f(2) = 3 + 4(2 - 1) = 3 + 4 = 7.

Substitute n = 3, 4 to get other terms as well.

So, we say f(n) = 3 + 4(n - 1) is the representation of the given arithmetic sequence.

User Brittnay
by
4.8k points